The Effect of Parental Involvement in Preventing Children's Behaviour Disorders - Abdul Hakim, Abdullah; Adamu, Zakiyu Ubale; kabara Auwal, Halabi (2016)
The supposition of this study is that involvement of parents in school events, which covers manifold positions of communication between parents and schools and a corporation in decision making, is advantageous for the educational and general progress of students. This article focused to explore the effect of parental involvement in preventing children’s behaviour disorders. The study is conceptual review, content analysis of the qualitative approach were used to accumulate information about the subject matter. The findings revealed that parental involvement help to prevent a children’s behaviour disorders. However, it also indicates that parent’s involvement do not only benefit the children’s educational performance but also influence in many aspects of their life including the way they behave. For that, government as well as private agencies have to work immensely to ensure the successful involvement of parents. Parents also have to understand that they are primarily needed to provide good citizens who are morally sound.